Regulatory factor X‐5/SCL/TAL1 interruption site axis promotes aerobic glycolysis and hepatocellular carcinoma cell stemness - Zhi‐Zhong Zhang; Zi‐Ming Wang; Hao‐Wen Zhang; Yan‐Xin Gong; Hao‐Ran Sun; Wei Zhang (Kaohsiung Journal of Medical Sciences)
Abstract The incidence and development of various tumors, such as hepatocellular carcinoma (HCC), are linked to tumor stem cells. Although research has revealed how important SCL/TAL1 interruption site (STIL) is in many human tumors, the impact of STIL on HCC stem cells is poorly understood. This study aimed to examine the regulatory mechanisms and the function of STIL in the stemness of HCC tumor cells. Bioinformatics analysis was applied to determine the STIL and regulatory factor X‐5 (RFX5) expression in HCC tissues. Immunohistochemistry (IHC) was used to detect the expression of STIL and RFX5 in HCC tissues. Quantitative real‐time polymerase chain reaction was utilized to measure the STIL and RFX5 expression levels in HCC cells. The viability of the cells was assessed by the Cell Counting Kit‐8 assay. The sphere formation assay was used to evaluate the sphere‐forming capacity. The expression levels of the stem cell markers SOX2, Oct‐4, CD133, CD44, the glycolysis‐related proteins LDHA, HK2, AKT, p‐AKT, and β‐catenin were assessed by Western blot. Lactate production, oxygen consumption rate, and extracellular acidification rate were measured to assess the glycolytic capacity of HCC cells. Chromatin immunoprecipitation and dual‐luciferase experiments were performed to validate the connection between RFX5 and STIL. Bioinformatics analysis determined that STIL exhibited high expression in HCC tissues and was enriched in the glycolysis pathway. In addition, the expression of glycolysis marker genes was positively correlated with STIL expression. Cell experiments verified that the activation of the glycolysis pathway by overexpression of STIL promoted stemness in HCC. Molecular experiments also revealed the binding relationship between STIL and RFX5. IHC detected high expression of STIL and RFX5 in HCC tissues. Cell functional experiments revealed that RFX5 could influence the HCC cells stemness by activating the STIL transcription via the glycolysis pathway. This study identified a novel role for the RFX5/STIL axis in HCC progression, which may offer treatment targets for HCC.